CHINESE NEW YEAR CANDLE BUSINESS IN TANAH GOCAP TANGERANG - Afifah, Inggrid Nur (Fakultas Sastra Universitas Darma Persada, 2023)
This article discusses Chinese ethnic culture in Lilin Ong business in Tanah Gocap, Tangerang. The author uses qualitative research methods, namely collecting data from the library, as well as observations and interviews with the owner of Lilin